The role of monetary incentives: Bonus and/or stimulus - Linda Ponta; Francesco Delfino; Gian Carlo Cainarca (Administrative Sciences, 2020)
In this paper, the role of the monetary incentives in the employee performance is investigated in the context of Public Administration (PA). In particular, the distribution of monetary incentives among the employees based on the position held, is compared with a merit approach which tends to recognize and reward individual contributions. Starting from a questionnaire, the informal network, which ignores the vertical relation among supervisor and employees, is created and a Centrality Index, based on the employee connections, has been defined and used to proxy the performance of employees. Themain goals of the paper are to understand if the twomechanisms ofmonetary incentive distribution affect the employee performance, to analyze the variables that influence the employee performance, and therefore to identify the role of monetary incentives. The linear regression methodology has been chosen as a tool of analysis. Results show that the distribution of monetary incentives according to merit criteria rewards the employee performance and has positive effects on the employee performance in the short term.
Keywords: 350; public administration; monetary incentives; organization; network